Present status of Salmonella Typhi in different age groups hospitalized patients in Duhok City, Iraq. - Muslim A Allu; Mahde S Assafi; Reem F Polse; Mohammad I Al-Berfkani (Zanco Journal of Pure and Applied Sciences, 2019)
Typhoid fever is still recognized as one of the most important global health problem. Salmonella species are the main cause of typhoid fever that causes health threat in developing countries. The purpose of this study was to find out the prevalence and the risk factors of Salmonella Typhi from people presenting with fever to Azadi general hospital, Duhok, Iraq. A total of 2323 patient blood samples (992 males and 1331 females) were collected through the period January 2017 to December 2017. Serologic-proved typhoid fever for Salmonella Typhi was diagnosed by Widal test. Out of 2323 blood samples, 824 (35.47%) were diagnosed as serologic-proved typhoid fever. The highest percentage (37.3%) of typhoid fever was recorded at age group 21–30 years and the less prevalence was at age group more than 51 years (29%) (p=0.4036). No significant differences was found in frequency of typhoid fever in males (35.4%) and females (35.5%) (p=0.9387). The incidence of typhoid fever in June (39%) was significantly higher than the incidence rate in other months of the year (p=0.0086). Typhoid fever has a considerable challenge to public health. The age group 21-30 years is the vulnerable group for typhoid fever. The typhoid fever is independent of sex and it is a seasonal disease with the majority of cases occurring is the June. Awareness should be created in young generation related to polluted water and hygienic food to eradicate this particular infection. Hence, health education classes play an important role in to reduce the infection rate.